Enzyme immunoassay of pancreatic oncofetal antigen (POA) as a marker of pancreatic cancer. Issue 5 (May 1985) - Nishida, K; Sugiura, M; Yoshikawa, T; Kondo, M
Abstract : For the quantitative measurement of pancreatic oncofetal antigen (POA), an enzyme immunoassay for POA has been developed, and is based on the sandwich method using antibody-coupled glass beads and enzyme (peroxidase)-labelled antibody. Serum POA concentrations were increased significantly in patients with pancreatic cancer, but not in those with chronic pancreatitis or other miscellaneous diseases, or in normal subjects. It is concluded that the enzyme immunoassay could be used for the assay of POA and our results show that the determination of serum POA would be useful in the diagnosis of pancreatic cancer.